Tatiana Aguilar-Álvarez Bay, Mariana Iglesias Arellano y Pedro Martín Aguilar (eds.), Círculos concéntricos. Lecturas críticas de la literatura española del siglo XX. UNAM, México, 2024; 372pp. - Valender, James (El Colegio de México, 2026)
Es una reseña